Smart Mobile Apps for Responsible Child Management: A Systematic Literature Review - Daniel Celestino; Harol Medina; Cristian Lara; Nemias Saboya (My University, 2025)
Children are increasingly using mobile devices, which raises challenges such as restricting access to inappropriate content, reducing excessive screen exposure, and ensuring safe digital habits. Although various parental control applications exist, most studies focus on isolated aspects such as content filtering or screen time management, with limited integration of artificial intelligence (AI) or consideration of children’s cognitive and emotional development. This highlights a research gap that requires a systematic review to consolidate existing evidence and identify best practices. Using the PRISMA methodology, a systematic search was conducted in four databases (Web of Science, Science@Direct, Scopus, and Semantic Scholar). After applying inclusion and exclusion criteria, 29 studies were selected for detailed analysis. Results show that AI-based applications can enhance personalization, improve detection of harmful content, and support parents in establishing healthier digital routines. However, limitations persist, including scarce training datasets, lack of algorithm transparency, and limited assessment of practical effectiveness. This review contributes by mapping current solutions, highlighting strengths and weaknesses, and providing evidence-based insights for researchers, parents, educators, and developers to design safer and more effective child-centered mobile applications.
Keywords: Computer science; Mobile apps; Systematic review; Human–computer interaction; World Wide Web; Data science; MEDLINE; Law; Political science; Computer science; Mobile apps; Systematic review; Human–computer interaction; World Wide Web; Data science; MEDLINE; Social Sciences Social Sciences Education Child Development and Digital Technology